The Emerging Role of PRMT6 in Cancer - Chen, Zhixian; Gan, Jianfeng; Wei, Zhi; Zhang, Mo; Du, Yan; Xu, Congjian; Zhao, Hongbo (Frontiers in Oncology, 2022)
Protein arginine methyltransferase 6 (PRMT6) is a type I PRMT that is involved in epigenetic regulation of gene expression through methylating histone or non-histone proteins, and other processes such as alternative splicing, DNA repair, cell proliferation and senescence, and cell signaling. In addition, PRMT6 also plays different roles in various cancers via influencing cell growth, migration, invasion, apoptosis, and drug resistant, which make PRMT6 an anti-tumor therapeutic target for a variety of cancers. As a result, many PRMT6 inhibitors are being utilized to explore their efficacy as potential drugs for various cancers. In this review, we summarize the current knowledge on the function and structure of PRMT6. At the same time, we highlight the role of PRMT6 in different cancers, including the differentiation of its promotive or inhibitory effects and the underlying mechanisms. Apart from the above, current research progress and the potential mechanisms of PRMT6 behind them were also summarized.